Dandelion Polysaccharide Exerts Anti-Angiogenesis Effect on Hepatocellular Carcinoma by Regulating VEGF/HIF-1α Expression - Ren, Feng; Wu, Kaixuan; Yang, Yun; Yang, Yingying; Wang, Yuxia; Li, Jian (Frontiers in Pharmacology, 2020)
Recent studies have revealed that natural plants-derived polysaccharides exhibit potent anti-tumor activity. Our earlier studies suggests that dandelion polysaccharide (DP) inhibits hepatocellular carcinoma (HCC) cell proliferation in vitro and in vivo. Here, we investigated the effects of DP on the angiogenesis of HCC and the potential molecular mechanisms by which DP regulates angiogenesis. Wound-healing and transwell invasion assays revealed that DP inhibited HUVECs migration and invasion in vitro, respectively. Tube formation assay, chick chorioallantoic membrane (CAM) assay, and immunohistochemistry (IHC) demonstrated that DP suppressed vasculogenesis in vitro and in vivo. Moreover, western blot and immunofluorescence staining verified that DP treatment decreased the protein levels of some key factors involved in angiogenesis of HCC, such as HIF-1α, VEGF, p-PI3K, and p-AKT. However, activation of PI3K/AKT pathway with IGF-1 treatment attenuated the effect of DP on angiogenesis via lowering the expression of HIF-1α and VEGF. In summary, we found that DP treatment inhibited angiogenesis in vivo and in vitro through suppressing expression of VEGF and HIF-1a. Furthermore, we showed that the expression of VEGF and HIF1-α was modulated by PI3K/AKT signaling. Collectively, our study suggests that DP is a promising anti-cancer drug candidate for treating HCC.